Paciente con tuberculosis pulmonar en tratamiento multidrogo resistente, sin apego al tratamiento. - Abigail Catherine, Martínez Haro (2019)
Pulmonary tuberculosis is a progressive chronic bacterial infection that mainly attacks the lungs, it is transmitted from person to person through breathing infected micro drops of air, this disease is preventable, treatable and curable, but could cause death if it is not treated in the right way and on time. In Ecuador, tuberculosis continues to be a health problem, occupying the eighth position in the region of the Americas, it registers 5,887 cases, of which 158 are cases of resistant tuberculosis, either due to abandonment of treatment, or due to drug resistance. first line due to bad use. This problem requires mainly the human talent to eradicate it, in this way as a government strategy we use the direct observation treatment system (DOTS), the objective is that the nursing staff based on the model of interrelation proposed by Hildegard Peplau, can perform a process of specific and personalized nursing care that meets the needs of the patient in a comprehensive manner, ensuring that the adherence to antituberculosis treatment is carried out naturally, and creating awareness in the patient and his support network, so that he can recover, without causing a drug resistance.